Ultra-high-field arterial spin labeling MRI for non-contrast assessment of cortical lesion perfusion in multiple sclerosis - Drury, Richard J.; Falah, Yasser; Gowland, Penny A.; Evangelou, Nikos; Bright, Molly G.; Francis, Susan T. (Springer, 2018)
Objectives